Aplikasi Penilaian Tingkat Kesehatan Unit Simpan Pinjam (USP) Koperasi Pegawai Republik Indonesia - Endang Sri Gunawati; Asteria Pudyantini (EKO-REGIONAL, 2011)
This research has the aims to analyze the health rate of KPRI KBK and KPRI MGR cooperative in Purworejo Regency and analyze owners equity development and their income after tax  during the period of 2007, 2008 and 2009. The research on cooperative health rate according to the Rule of The State Minister of Cooperative and KUKM is based on 7 (seven) aspects, they are capital, the quality of productive assets, management, efficiency, liquidity, self sufficiency and growth and cooperative identity. Besides that this research also aims to analyze owners equity development and its income after tax from   KPRI KBK and KPRI MGR cooperative in Purworejo Regency.  The data include the financial report of KPRI KBK and KPRI MGR cooperative in Purworejo Regency during the period 2007, 2008 and 2009.The rule of The State Minister of Cooperative and Small and Medium Business No14/Per/M.KUKM/XII/2009, December 22nd 2009 is used to analyze the health rate of KPRI KBK and KPRI MGR cooperative in Purworejo Regency. The total scores received from the calculation is used to determine the health rate of KPRI KBK and KPRI MGR in Purworejo Regency and then to analyze the development of owners equity and income after tax, linear trend is applied. The result of analysis shows that the health rate of KPRI KBK in Purworejo Regency during the period of 2007, 2008 and 2009 has got the predicate of “Sufficient Healthy” as during the three years continuously has got the score of 75.00; 74.00 and 74.00 (the scores are located between 60 ≤ X ≤ 80), whereas KPRI MGR cooperative in Purworejo Regency during the period of 2007, 2008 and 2009 also has got the predicate of Sufficien Healthy as within the period of three years continuously has got the scores of 70.40; 68.90 and 69.00. From the analysis af the development of owners equity and income after tax during the period 2007, 2008 and 2009, it has got the result that whether KPRI KBK or KPRI MGR cooperatives in Purworejo Regency, there is an increasing tendency of their owners equity and income after tax. Finally based on the result of research, KPRI KBK cooperatives in Purworejo Regency has to increase the component that can increase owners equity such as increasing the amount of depositfrom its members. Besides that KPRI KBK cooperatives in Purworejo Regency have to open long term deposit or credit facilities with competitive and  the decreasing the operating costs in order to incease efficiency assessment aspect in the ratio of operating income towards brutto income after tax. The Departement of Cooperative has to carry out the socialization of cooperative health evaluation perriodically and regularly so the cooperatives available can make a self assessment on their saving and borrowing units and the can overcome the problem when there is decreasing score on cooperative assessment. Keywords: evaluation of cooperative health rate, owners equity and net income after tax.